Development of Education for Sustainable Development (ESD)-Based E-Module on the Topic of Biochar to Train Students’ Science Literacy - Shilla Aulia Suhandi; Ali Kusrijadi; Asep Supriatna (Jurnal Pendidikan dan Pembelajaran Kimia, 2026)
Development of Education for Sustainable Development (ESD)-Based E-Module on the Topic of Biochar to Train Students' Science Literacy. This study aims to develop an e-module based on Education for Sustainable Development (ESD) on the topic of biochar to train students' science literacy. The research method employed the Design and Development (DDR) Type 1 approach, following specific project phases: analysis, design, development, and evaluation, including a limited pilot test. The study involved nine 11th-grade students at a high school in Bandung. Data were collected using validation sheets for the core text, practice exercises, evaluation questions, and student response analysis. The results indicate that the ESD-based e-module product on the topic of biochar is valid for instructional use. Furthermore, the student profile science literacy assessment revealed a good achievement level across all measured aspects of science literacy after using the e-module. The developed ESD-based e-module on the topic of biochar is a valid and effective tool that has significant potential to train students' science literacy in chemistry education.